The forgotten development: A discussion about the clean development mechanism and socioenvironmental sustainability - Sanches-Pereira, Alessandro (WIT PRESS, 2007)
The concept of sustainable development (SD) has been broadened to become a new paradigm and form a hope for human impact mitigation. There is some consensus around its implementation; however, the imprecision of the SD concept causes worldwide debates regarding the diversity of adoption and understanding. In this context, the question is how we can shape the development process in order to make it capable of taking into consideration the local way of becoming sustainable. One recent attempt is the clean development mechanism (CDM) concept. This faces similar problems because the way in which the mechanism is used today does not fulfil its goal of assisting SD. Generally the mechanism is used only to meet the terms for emission reduction described in Article 3 of the Kyoto Protocol and does not contribute to the local society development. Consequently, it is necessary to develop a strategic plan for CDM's future implementation and repair its design failures by evaluating its current performance. An effective mechanism must integrate the socioenvironmental development concept into the implementation strategy. As a result, the new CDM must not only promote strict environmental sustainability, but also contribute to the reduction of poverty and social inequalities. This is because CDM will not be successful in the long term if it does not achieve the integration of social development with reduction of emissions. © 2007 WIT Press.